TOXIN BOTULINUM: REVIEW OF GENERAL ASPECTS AND EVIDENCE OF ITS DIRECT ANALGESIC EFFECT - Luiza Ribeiro de Almeida, Bruna; Giacomini, Alex; Geremias Chichorro, Juliana (Health and Society, 2022)
Botulinum neurotoxins (BoNT) are toxins produced by bacteria of the genus Clostridium botulinum and are considered as the most potent toxins nowadays. Firstly, known as a food poison, later explored as a biological weapon and currently considered a great therapeutic resource. Seven different BoNT serotypes (A-G) have already been identified. Among them, serotypes A and B are used in clinics, and serotype A is the most used for the highest efficacy and safety. BoNT is widely known and used in aesthetics, through intramuscular injections to attenuate dynamic wrinkles. Additionally, it has been used as therapy in the treatment of strabismus, blepharospasm, cervical dystonia, hyperhidrosis, sialorrhea, hemifacial spasm, and many other clinical conditions in areas such as urology, neurology, ophthalmology, gastroenterology and more recently evaluated in psychiatry. BoNTs are also being studied for a new therapeutic horizon: the treatment of pain. In some painful syndromes that can be treated with BoNT, the mechanism of action is related to the inhibition of muscle contraction through inhibition of acetylcholine release at the neuromuscular junction. This effect involves a selective toxin action on SNARE family proteins (soluble N-ethylmaleimide sensitive factor attachment protein receptor), which mediate the acetylcholine exocytosis process. Moreover, it shows analgesic effect in some clinical conditions that are not related to excessive muscle contraction, such as in the treatment of migraine. Therefore, it has been suggested that BoNT is capable of producing analgesia independent of muscle contraction inhibition. This evidence has stimulated the study of BoNT in other painful conditions, such as trigeminal neuralgia. One of the advantages of BoNT clinical application is its safety. Major adverse effects are application-related and include pain, erythema, pruritus, edema, bruising, hematoma, paraesthesia, and ptosis. In this review BoNT will be analyzed in the historical, pharmacological, biochemical and clinical aspects, but the focus will be on the investigation of the analgesic effect of BoNT that occurs regardless of its muscle relaxant effect.